2010
DOI: 10.1016/j.juro.2009.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy Induced Chronic Renal Insufficiency is Associated With Increased Risk of Cardiovascular Death and Death From Any Cause in Patients With Localized cT1b Renal Masses

Abstract: Partial nephrectomy offers cancer specific survival equivalent to that of radical nephrectomy and is technically feasible in at least 50% of patients with cT1b tumors. Preservation of renal function was significantly better in patients treated with partial nephrectomy. Postoperative renal insufficiency was a significant independent predictor of overall and cardiovascular specific survival, and efforts should be made to limit the renal function loss associated with surgery for localized renal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
234
3
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(258 citation statements)
references
References 27 publications
7
234
3
14
Order By: Relevance
“…Patients with radical nephrectomy-induced chronic renal insufficiency have a 25% increased risk of cardiac death and a 17% increased risk of death from any cause compared to patients undergoing nephron preservation surgery for cT1b tumours [2].…”
Section: Trends In the Surgical Management Of Localized Renal Massesmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with radical nephrectomy-induced chronic renal insufficiency have a 25% increased risk of cardiac death and a 17% increased risk of death from any cause compared to patients undergoing nephron preservation surgery for cT1b tumours [2].…”
Section: Trends In the Surgical Management Of Localized Renal Massesmentioning
confidence: 99%
“…Of the 413 patients treated with BT, 166 were aged <65 years. The 10-year SM-free survival for the whole BT-treated group was 87%, which was not significantly different from that of the cohort treated with radical prostatectomy (P = 0.37), Their multivariate analysis suggested that older age (P = 0.01) and history of smoking (P < 0.001) were significant predictors for the development of an SM, whereas treatment intervention was not a significant variable.Our group have recently presented data on 76 patients under the age of 55 with localized prostate cancer treated with BT-based regimens [2]. The actuarial 8-year PSA-free survival was 96%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This trend has been attributed to the growing number of small renal masses incidentally detected on cross-sectional imaging performed for non-urologic conditions [3]. With this trend, treatment with partial nephrectomy (PN) has seen widespread use [4][5][6] as a means to avoid the sequelae of surgically induced chronic kidney disease associated with radical nephrectomy (RN) [7][8][9][10]. In fact, current guidelines from the American Urological Association (AUA) [11], National Comprehensive Cancer Network (NCCN) [12••], and European Association of Urology (EUA) [13••] now promote the use of PN whenever technically feasible for the treatment of small renal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In addition, based on primarily retrospective data identifying radical nephrectomy as a significant risk factor for chronic kidney disease. [4] Due to the small size, early stage of tumors and advanced surgical techniques, surgeons were able to perform partial nephrectomies without sacrificing safety and oncology efficiency. [5] However, despite the use of partial nephrectomy some patients still progressed to chronic kidney disease.…”
mentioning
confidence: 99%